Lyophilized Symbiotic Mitigates Mucositis Induced by 5-Fluorouracil - Savassi, Bruna; Cordeiro, Bárbara F.; Silva, Sara H.; Oliveira, Emiliano R.; Belo, Giovanna; Figueiroa, Alessandra Gomes; Alves Queiroz, Maria Izabel; Faria, Ana Maria Caetano; Alves, Juliana; Silva, Tales Fernando da; Campos, Gabriela Munis; Esmerino, Erick A.; et al. (Frontiers in Pharmacology, 2021)
Mucositis is an adverse effect of cancer chemotherapies using 5-Fluorouracil (5-FU). It is characterized by mucosal inflammation, pain, diarrhea and weight loss. Some studies reported promising healing effects of probiotic strains, when associated with prebiotics, as adjuvant treatment of mucositis. We developed a lyophilized symbiotic product, containing skimmed milk, supplemented with Whey Protein Isolate (WPI) and with fructooligosaccharides (FOS), and fermented by Lactobacillus casei BL23, Lactiplantibacillus plantarum B7 and Lacticaseibacillus rhamnosus B1. In a mice 5-FU mucositis model, this symbiotic lyophilized formulation was able to reduce weight loss and intestinal permeability. This last was determined in vivo by quantifying blood radioactivity after oral administration of 99mTc-DTPA. Finally, histological damages caused by 5-FU-induced mucositis were monitored. Consumption of the symbiotic formulation caused a reduced score of inflammation in the duodenum, ileum and colon. In addition, it decreased levels of pro-inflammatory cytokines IL-1β, IL-6, IL-17, and TNF-α in the mice ileum. The symbiotic product developed in this work thus represents a promising adjuvant treatment of mucositis.